The role of cloud accounting in improving the accounting profession from the perspective of faculty members (A field study in the Accounting Department, Faculty of Economics, Al-Merqib University) (Economic studies journal, 2024)
The study aims to identify the role of cloud accounting in improving the accounting profession in Libya, and to identify the current status of cloud accounting in Libya, in addition to the extent to which academics in Libya are aware of the concept of cloud accounting, its objectives, and the dimensions of its application in Libya. The problem of the study was represented in a main question: What is the role of cloud accounting?, Cloud accounting in improving the accounting profession from the point of view of faculty members in the Accounting Department, Faculty of Economics, Al-Merqib University, To achieve the purposes of the study, the descriptive and analytical approach was used, using statistical methods to present and analyze the results of the study. The study concluded with many results, the most important of which are: Academics are aware of the advantages and characteristics of cloud accounting, for its role in improving the accounting profession, through its contribution to helping the accountant prepare accounts with the least time and effort, and the possibility of accessing information at any time and from anywhere. Academics are aware of the importance of cloud accounting, its objectives, and the dimensions of its application, for its role in Improving the accounting profession, through the application of cloud accounting, increases the confidence and satisfaction of information users, In addition, the application of cloud accounting helps accountants innovate and be creative by developing their skills. The study presented several recommendations, including: The necessity of relying on successful software that guarantees the security and integrity of customer-related data and preventing it from being hacked or accessed, and working to develop curricula in Libyan universities to keep pace with technical developments and in a way that contributes to learning about the concept and advantages of cloud accounting, and spreading awareness of the importance and advantages of cloud accounting and its various applications and the feasibility of its use.
Keywords: loud Accounting; inancial Performance; Accounting Profession